Bacteriological Study on Dental Caries and Test their Sensitivity to Virulence Factors and Heavy Metals - Ali, Muna Jalal; Makky, Essam A.; M. M., Yusoff (AENSI, 2015)
Tooth decay is considered the most widespread infectious disease in the world. This study aims to isolate and identify the important bacteria related to tooth decay, determine the sensitivity of bacteria in certain types of antimicrobial agents, and study the effect of heavy metals on bacterial isolates. A total of 50 swabs were collected from the mouths of patients from both gender, with ages ranging from 3–60 years. The patients were advised to consult with dental clinics and specialized centers to isolate and identify the causative agents associated with oral diseases. Results showed that infection rates in younger age groups (3–20 and 20–40) are higher than the elder group (40–60), with percent incidence of 44% and 32%, respectively. Heavy metals sensitivity test against the oral isolates were found lower effect for isolates against (15) heavy metals, where it showed resistance to Iron 3.38% , then nickel, aluminum,copper, lead to 20.33%, 22.03%, 27.11%, 28.81% respectively, also sliver shown 57.62%. And, this similarity were found have sensitive to antimony and chromium 61.01%.while appeared sensitivity to mercury and cadmium by 100, 86.44%. Hemolysin had the highest ability to produce virulence factors (72.88%), followed by lecithinase (42.37%) and protease (25.42%). Lipase and urease had the lowest virulence factor production (10.16%).